Synergistic effects of iron powder on intumescent flame retardant polypropylene system (eXPRESS Polymer Letters)
The effects of iron powder as a synergistic agent on the flame retardancy of intumescent flame retardant polypropylene composites (IFR-PP) were studied. The thermogravimetric analysis (TGA) and cone calorimeter (CONE) were used to evaluate the synergistic effects of iron powder (Fe). The TGA data showed that Fe could enhance the thermal stability of the IFR-PP systems at high temperature and effectively increase the char residue formation. The CONE results revealed that Fe and IFR could clearly change the decomposition behavior of PP and form a char layer on the surface of the composites, consequently resulting in efficient reduction of the flammability parameters, such as heat release rate (HRR), mass loss (ML), Mass loss rate (MLR), total heat release (THR), carbon monoxide and so on. Thus, a suitable amount of Fe plays a synergistic effect in the flame retardancy of IFR composites.